SAT0006 Polymorphisms in STAT4, IL10, PSORS1C1, PTPN2 and MIR146A Genes Are Differently Associated with Negative Prognostic Factors in Italian Patients Affected by Rheumatoid Arthritis. (15th July 2016) - Conigliaro, P.; Perricone, C.; Ciccacci, C.; Rufini, S.; Triggianese, P.; Politi, C.; Latini, A.; Novelli, G.; Borgiani, P.; Perricone, R.
Abstract : Background: Rheumatoid Arthritis (RA) is a systemic autoimmune disease resulting in chronic inflammation of the synovium and consequent cartilage and bone erosion. RA is strongly associated with the presence of rheumatoid factor (RF) and consists of clinical subsets of anti-citrullinated protein antibody (ACPA)-positive and negative patients. Several genes have been proven to contribute to the disease susceptibility and they may be associated with a particular pattern of disease and with the response or toxicity to therapy. It is important to identify novel genomic biomarkers associated not only with disease susceptibility but also able to detect early those patients with negative prognostic factors who may benefit from a more aggressive therapeutic approach. Objectives: This study was designed to evaluate whether the most relevant single nucleotide polymorphisms (SNPs) associated with RA and other autoimmune disorders are related to RF, ACPA, and clinical phenotype in a cohort of biologic-naïve Italian RA patients. Methods: A total of 192 RA patients [female n=147 (76.5%), age 54.1 ± 13.2 years, disease duration 7.8 ± 9 years, positive RF n=130 (67.7%), positive ACPA n=137 (71.7%), 28 joint count disease activity score (DAS28) 5.2 ± 1.3, bone erosions at diagnosis n=69 (60%), disease modifying anti-rheumatic drugs (DMARDs) n=148 (77.1%)] were enrolled. 278 age-matched healthy controls were included. We analyzed a total of 12 SNPs in STAT4, IL10, PSORS1C1, PTPN2, ERAP1, TRAF3IP2 and MIR146A genes by allelic discrimination assays. Case-control association studies and genotype/phenotype correlation analyses were performed (Figure 1 A-B). Results: A higher risk to develop RA was observed for rs7574865 in STAT4 gene (P=0.035, OR=1.41). We observed a significant association between the variant alleles of rs1800872 in IL-10 gene and RA susceptibility. Subjects carrying the variant alleles (in heterozygous and homozygous status) showed a lower risk to develop RA in comparison with wildtype individuals (P=0.014, OR=0.63). The presence of RF resulted significantly associated with rs1800872 variant in IL10 (P=0.032, OR=2) while rs2910164 in MIR146A was protective (P=0.05, OR=0.55). ACPA were significantly associated with rs7574865 in STAT4 (P=0.004, OR=2.64). The SNP rs2233945 in PSORS1C1 gene was protective regarding the presence of bone erosions (P=0.042, OR=0.44) while rs2542151 in PTPN2 gene was associated with joint damage (P=0.044, OR=3.26). Conclusions: Our results confirm that polymorphisms in STAT4 and IL10 genes confer susceptibility to RA. For the first time we described that SNPs in PSORS1C1, PTPN2 and MIR146A genes were differently associated with a severe disease phenotype in terms of autoantibody status and radiographic damage in an Italian RA population. Disclosure of Interest: None declared